Molecular imprinting of 5-fluorouracil in particles with surface RAFT grafted functional brushes - Oliveira, Daniela (2017)
Molecularly imprinted particles with surface grafted functional polymer brusheswere synthesized and evaluated aiming at the targeting of 5-fluorouracil (5-FU). A molecular imprinting material for 5-FU was prepared through precipitation crosslinking polymerization, in the presence of a RAFT agent, and choosing either methacrylic acid (MAA) or 2-hydroxyethyl methacrylate (HEMA) as functional monomers. In a later step, different kinds of functional polymer brushes, namely poly(methacrylic acid), poly(2-hydroxyethyl methacrylate) and poly(Nisopropylacrylamide) were grafted in the particles through a “grafting from” process starting on the RAFT groups present in their surface. The accomplishment of 5-FU imprinting was proven through comparative drug uptake measurements with imprinted/non-imprinted materials. Enhancement of 5-FU release in alkaline conditions comparatively to acidic environmentswas shown for particleswith different combinations of molecular imprinting and grafted functional brushes. TheMAA imprinting systemwith PMAA grafted functional brushes shows the highest improvement in 5-FU release triggered by a pH change from 2 to 10. Furthermore, for particles with PNIPA grafted brushes, a boost in drug release was also shown at T = 20 °C as compared to 40 °C. The novel achievements reported here put into evidence the combined benefits of molecularly imprinted particles with surface grafted functional polymer brushes concerning molecular recognition and stimulated 5-FU release.